School-Based Decision-Making As A Predictor Of Effective School Administration In Enugu State, Nigeria: Implications For Psychology And Measurement Experts - Aguiyi, Chinwe Faith Diara, Deborah Julius Agwu, Chioma Madu, Cornelius Chukwuebuka; Ukpai, Fidelis Eze Amaeze, Theresa Chinma Agodo, Grace Nkolika Anigbogu, Francis Elochukwu Ikeh, Eke N. (Metallurgical and Materials Engineering, 2025)
The study investigated school-based decision-making as a predictor of effective school administration in Enugu State, Nigeria. The study was guided by four research questions and corresponding four hypotheses. Methods: The study adopted a correlation survey design with a population of 7,790 teachers in 286 public senior secondary schools in Enugu State, Nigeria. Two instruments titled School-Based Decision-Making Questionnaire (SBDMQ) and Effective School Administration Questionnaire (ESAQ) were used for data collection. The validity of the instruments where determined through confirmatory factor analysis and the output showed that the items have values above 3.0 Eigen Value. The internal consistency reliability type through Cronbach Alpha gave reliability coefficients of .78, .81 and .83 for the clusters of strategic school-based decision making, tactical school-based decision making and operational school-based decision making. Moreso, the reliability coefficients of .88 and .91 were established for School-Based Decision-Making Questionnaire (SBDMQ) and Effective School Administration Questionnaire (ESAQ) respectively. Linear and multiple regression were used to answer the research questions while regression t-test and Analysis of Variance (ANOVA) were used to test the hypotheses at 0.05 significant level. Results: The study showed that strategic school-based decision making to a moderate extent predicted effective school administration in secondary schools in Enugu State, Nigeria. The study showed that tactical school-based decision making to a moderate extent predicted effective school administration in secondary schools in Enugu State, Nigeria. The study showed that operational school-based decision making to a moderate extent predicted effective school administration in secondary schools in Enugu State, Nigeria. Conclusion: Based on the findings of this study, it was concluded that school-based decision-making are significant determinants of effective school administration in Enugu State, Nigeria. The study also concluded that strategic, tactical and operational school-based decision making are indispensable in the achievement of effective school administration in Enugu State. Recommendations: School principals should promote inclusive decision-making by actively involving teachers, staff, and other stakeholders in school decisions. This will enhance commitment, accountability, and effectiveness in administration; Government and educational authorities should organize regular training, workshops, and seminars for principals and school leaders on strategic, tactical, and operational decision-making skills to improve administrative competence.